STM information. Multidisciplinary products and services in 2010 - Maldonado-Martínez, Ángeles (Anuario ThinkEPI, 2011)
Review of the status of scientific information market in 2010. Presentation of the most relevant multidisciplinary products and services. All major platforms, journal aggregators, bibliographic databases, open access repositories and academic search engines are reviewed.
Keywords: Information market; Scientific information; Scholarly information; Information sources; Information products; Information resources